2015
DOI: 10.3168/jds.2015-9893
|View full text |Cite
|
Sign up to set email alerts
|

Peripartal changes in reticuloruminal pH and temperature in dairy cows differing in the susceptibility to subacute rumen acidosis

Abstract: The present study aimed to investigate changes in the reticuloruminal pH and temperature dynamics in periparturient dairy cows. Reticuloruminal pH and temperature measurements were conducted from 7 d before until 8 d after parturition using indwelling sensors. Nine Simmental and 4 Brown Swiss dairy cows were fed a close-up total mixed ration (52.5% neutral detergent fiber, 5.68MJ of net energy for lactation per kg of dry matter) with additional 1kg/cow per d concentrate mixture (29.5% neutral detergent fiber a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 30 publications
4
28
0
1
Order By: Relevance
“…() found a negative correlation between ruminal temperature and pH and concluded that a ruminal temperature between 39 and 41°C is critical for the diagnosis of SARA. However, other studies using sensors located in the reticulum found no correlation between the ruminal pH and temperature (Bodas et al., ; Humer, Ghareeb et al., ). We recently measured reticular pH as well as reticular and rectal temperature in dairy cows exposed to an intermittent SARA challenge.…”
Section: Interpretation Of Ruminal Temperaturementioning
confidence: 90%
“…() found a negative correlation between ruminal temperature and pH and concluded that a ruminal temperature between 39 and 41°C is critical for the diagnosis of SARA. However, other studies using sensors located in the reticulum found no correlation between the ruminal pH and temperature (Bodas et al., ; Humer, Ghareeb et al., ). We recently measured reticular pH as well as reticular and rectal temperature in dairy cows exposed to an intermittent SARA challenge.…”
Section: Interpretation Of Ruminal Temperaturementioning
confidence: 90%
“…Nevertheless, as ruminal pH is also affected by neutralisation processes (Aschenbach et al, 2011), these factors might also contribute to rumen health and metabolic adaptation of periparturient dairy cows. We have recently demonstrated that transition dairy cows show different responses of ruminal pH despite similar feeding management (Humer et al, 2015a), posing them at different risks of rumen fermentation disorders postpartum. Moreover, researches over the last years suggested a large variation among dairy cows in the release of stored energy from adipose tissues (Weber et al, 2013;Rico et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…SARA has negative economic impact on dairy production due to the association with decreased feed intake (Nagaja and Lechtenberg, 2007), diarrhea, laminitis (Nocek, 1997) and milk fat depression (Kleen et al, 2003). Early diagnosis of SARA during the transition period is important to prevent complications at an early stage and enhance cow health (Humer et al, 2015). Buttchereit et al (2010) reported that F/P ratio reflects the energy balance status of a cow in early lactation.…”
mentioning
confidence: 99%